Minimum wages and firm profitability - Mirko Draca; Stephen Machin; John Van Reenen (Institute for the Study of Labor (IZA), 2006)
Although there is a large literature on the economic effects of minimum wages on labour market outcomes (especially employment), there is hardly any evidence on their impact on firm performance. This is surprising: minimum wages appear to have a significant impact on wages, but only a limited impact on jobs, so it is natural to imagine there must be a stronger impact on other aspects of firm behaviour. In this paper we consider the impact of minimum wages on firm profitability by exploiting the introduction of a minimum wage to the UK labour market in 1999. We use pre-policy information on the distribution of wages to construct treatment and comparison groups and implement a difference in differences approach. We show evidence that firm profitability was significantly reduced (and wages significantly raised) by the minimum wage introduction. This emerges from separate analyses of two distinct types of firm level panel data (one on firms in a very low wage sector, UK residential care homes, and a second on firms across all sectors). Interestingly, we find no evidence that the profitability reductions resulted in increases in firm exit, so our findings may be consistent with redistribution of quasi-rents towards low wage employees.
Keywords: J23; L25; 330; minimum wage; profitability; exit; Arbeitsmarkt; Mindestlohn; Rentabilität; Unternehmen; Schätzung; Großbritannien